Knowledge of Trafficking in Human Beings among Portuguese Social Services and Justice Professionals - Cunha, Ana (European journal on criminal policy and research, 2019)
Knowledge about trafficking in human beings has several implications for various social service and justice professionals. The aim of this study was to examine the knowledge of social service and justice professionals regarding the characterization of this phenomenon and anti-trafficking policies in Portugal. Four hundred and forty-six social service and justice professionals completed an online Human Trafficking Knowledge survey. The results revealed that Portuguese professionals have, in general, a good level of knowledge about trafficking in human beings, revealing higher-level scores for issues, such as trafficking in human beings' idiosyncrasies and purposes in Portugal, trafficker profiles, criminal behaviour, victim profiles and victimization dynamics. On the other hand, participants scored lower in trafficking in human being's trajectories and specificities within Portugal. This knowledge appeared to be influenced by variables, such as professional experience, previous contact with trafficking and training in trafficking in human beings. National policies must promote professional formal training about trafficking in human beings in different areas.